Pretreatment Stress Enhances Embryogenic Callus Production in Anther Culture of Sturt Desert Pea (Swainsona formosa) - ZULKARNAIN ZULKARNAIN (HAYATI Journal of Biosciences, 2007)
The aims of the experiment were to investigate the effect of pretreatment stress on the proliferation of anther-derived embryogenic callus, and its subsequent embryo regeneration in Swainsona formosa. Anthers were pretreated in starvation medium at cold (4 0C) temperature and cultured. Cultures were initially placed in darkness for four weeks, followed by 16-h photoperiod at 25 + 1 0C. The stress pretreatment was found to enhance embryogenic callus formation on cultured anthers. Further, somatic embryos were successfully regenerated from embryogenic callus upon transferred onto regeneration medium supplemented with 1% sucrose and 4.63 uM kinetin, and later plantlets were obtained. Meanwhile, nonembryogenic callus continued to grow resulting in more callus mass without showing any embryoid initiation. Key words: anther culture, embryogenic callus, stress pretreatment, Swainsona formosa